Konsep Pratical Fun pada Mebel Multifungsi Anak Usia Dini untuk Hunian Terbatas di Surabaya - Agustine Indriani (Intra, 2017)
Due Due to the change of habittation pattern and lifestyle in metropolis city like surabaya, society this day tend to choose limited occupancy living spacesuch as apartment. This limitation on space would affect  couples who has a 0 to 8 years old child that need a lot of space for their playing activity and learning facility. The solution for this problem is to have a multifunctional  furniture  that suitable for the playing activity and learning in home with practical fun concept which has three main values in designing such as playable, useful, and enjoyable refering to the character of the child. Inspiration, ideation, and implementation are the three design thinking stages being used in the design research. and from these three steps, the design process extended to understanding, observe, pay, ideate, prototype, story telling, pilot, and business model. This design process was  analyzed  from the shape, function, psychological, and ergonomics aspect that presented on the design  through the three alternatives in the multifunctional furniture.there are three sets of related products  In every of each furniture that fullfil the activity and facility needs of the child according to the development.The outcome of thus design practices are three sets of sleeping set, sitting set, and storage set which has a function of baby highchair, babywalker, child seat, baby crib, baby tafel, play yardchildbed, single sized bed, wardrobe, toy rack, book rack, whiteboard, study desk, and playing desk. Moreover, there is an educational based game that focused on language, math, shape,  and music.